Digital culture as an innovative component of a teacher's professional activity - Alexandra Vladimirovna Leontyeva; Natalya Vladimirovna Kovaleva; Fatima Ramazanovna Khatit (Вестник Майкопского государственного технологического университета, 2023)
Professional activity in the digital environment is an integral component of modern life in Industry 4.0. The success of the formation of digital competence of an individual in modern realities is largely determined by the level of digital culture of a teacher himself as a translator of the values of the digital society. In this regard, the problem of the research can be formulated as follows: what are the theoretical approaches to substantiating the category of "digital culture" in modern pedagogical discourse?The purpose of the research is to reveal the essence of the concept of "digital culture" as an actual pedagogical category. The research methods used are analysis, synthesis, differentiation, description.The results of the study are based on the analysis and synthesis of derivatives of the definition of "digital culture". Theoretical approaches to the content of the concept of "digital culture" as an innovative component of the teacher's professional activity have been presented; the concept of "digital culture" has been clarified; the basic components of a teacher's digital culture have been proposed.The key conclusions are the following: derivatives of the definition of "digital culture" are "digital literacy", "digital competence", ICT culture; The digital culture of a teacher is understood as the formation of the necessary skills for successful functioning in mixed reality, including the skills of safe and effective work with content, communication with other users in the electronic educational environment, search and consumption of information, continuous improvement, motivational and value attitude to the digital service, providing ergonomic functioning in the new digital educational space; the basic components of a teacher's digital culture are: digital literacy, ICT competencies, motivational-value attitude.